Parent Risk Perceptions, Physical Literacy, and Fundamental Movement Skills in Children With Juvenile Idiopathic Arthritis. Issue 4 (12th October 2022) - Brandelli, Yvonne N.; Stone, Michelle; Westheuser, Victoria; Huber, Adam M.; Joshi, Nila; Reid, Allison; Stringer, Elizabeth; Stevens, Daniel
Abstract : Purpose: This pilot study sought to examine the fundamental movement skills (FMS) and physical literacy (PL) of children with juvenile idiopathic arthritis (JIA) and to explore their relationship with physical activity (PA) and parent perceptions of PA-related risks. Methods: Twenty-five children with JIA and their parents completed questionnaires. Fundamental movement skills were assessed in the laboratory and PA through accelerometry data. Results: Children spent a median of 39.4%, 40.9%, and 18.2% of their day sedentary, in light, and in moderate to vigorous PA, respectively. Fundamental movement skills and PL scores were within the average range, although were related to which joints (upper/lower body) were affected by JIA. Parents who viewed activities such as biking and climbing as risky tended to have children with weaker locomotor skills and lower PL. Conclusion: Children with JIA had age-appropriate PA, FMS, and PL; however, parent perceptions of PA-related risks are related to their child's FMS and PL.